The product of a thyroid hormone-responsive gene interacts with thyroid hormone receptors - Thompson, Catherine C. (The National Academy of Sciences of the USA, 1997)
Thyroid hormone is a critical mediator of central nervous system (CNS) development, acting through nuclear receptors to modulate the expression of specific genes. Transcription of the rat hairless (hr) gene is highly up-regulated by thyroid hormone in the developing CNS; we show here that hr is directly induced by thyroid hormone. By identifying proteins that interact with the hr gene product (Hr), we find that Hr interacts directly and specifically with thyroid hormone receptor (TR)—the same protein that regulates its expression. Unlike previously described receptor-interacting factors, Hr associates with TR and not with retinoic acid receptors (RAR, RXR). Hr can act as a transcriptional repressor, suggesting that its interaction with TR is part of a novel autoregulatory mechanism.